Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS) and Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS): Immunological Features Underpinning Controversial Entities - Lucia Leonardi; Camilla Perna; Irene Bernabei; Marco Fiore; Meiqian Ma; Jennifer Frankovich; Luigi Tarani; Alberto Spalice (MDPI AG, 2024)
Pediatric acute-onset neuropsychiatric syndrome (PANS) and Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS), represent an overlapping group of disorders which is characterized by acute-onset obsessive compulsive disorders, eating restriction, tics, cognitive and behavioral deterioration which typically follows a relapsing-remitting course but some patients have a primary or secondary persistent progress. This condition is likely caused by heterogeneous inflammatory mechanisms (autoantibodies, complement activation, pro-inflammatory cytokine production) involving the basal ganglia as evidenced by imaging studies (patients vs. controls), sleep studies that found movements and/or atonia during REM sleep, and neurological soft signs that go along with basal ganglia dysfunction. The condition causes significant psychiatric and behavioral symptoms, caregiver burden and sleep abnormalities. Autoantibodies resulting from molecular mimicry of infectious agents (namely group A Streptococcus) and neuronal autoantigens that map to the basal ganglia play also a subtle role. This narrative review aims to describe the key immunological features documented thus far and that likely play a role in the pathogenesis and clinical manifestations of this disorder.